CYP2C19 genotyping combined with on-clopidogrel platelet reactivity in predicting major adverse cardiovascular events in Chinese patients with percutaneous coronary intervention. Issue 147 (November 2016) - Tang, Xiao-Fang; Han, Ya-Ling; Zhang, Jia-Hui; Wang, Jing; Yao, Yi; He, Chen; Xu, Bo; Gao, Zhan; Qiao, Shu-Bin; Chen, Jue; Wu, Yuan; Chen, Ji-Lin; et al.
Abstract: Introduction: Both CYP2C19 genotyping and platelet function testing are used to predict major adverse cardiac events (MACEs) in Chinese patients treated with clopidogrel and undergoing stent implantation, but the most accurate prognostic technique is still debated. Here, we combine both techniques, to determine if a more accurate prognosis is possible. Methods: Patients undergoing stent implantation (1104) were genotyped and assessed for platelet reactivity, with a 12-month follow-up. The CYP2C19*2 (rs4244285), and *3 (rs4986893) alleles were genotyped. High on treatment platelet reactivity was defined as adenosine diphosphate (ADP)-induced platelet inhibition ≤ 30%. MACEs included death, nonfatal myocardial infarction, target vessel revascularization, or stent thrombosis. Results and conclusions: Hazard ratios (HRs) for cardiovascular ischemic outcomes based on the two testing methods are as follows. CYP2C19 genotyping: carriers of CYP2C19 loss-of-function alleles, HR: 2.515, 95% confidence interval (CI), 1.150–5.501, P = 0.021; ADP-induced platelet inhibition ≤ 30%, HR: 1.992, 95% CI, 1.040–3.818, P = 0.038. An ischemic risk score between zero and two was calculated. Compared with the group with a score of zero, HRs for adverse cardiovascular outcomes were 4.078 for those with a score of two (95% CI: 1.525–10.905, P = 0.005). However, there was no significant difference between the group with the score of zero and the group with the score of one. CYP2C19 genotyping combined with platelet reactivity is an independent and additive predictor of 1-year MACE in Chinese patients undergoing stenting with clopidogrel treatment, which is better than either test alone. Highlights: CYP2C19 genotyping or on-clopiodgrel platelet reactivity was an independent risk predictor of MACEs in Chinese patients. The aggregate positive results based on the two testing methods were a more powerful predictor of higher risk. The aggregate positive results showed independent and additive prognostic values for MACEs in patients undergoing PCI.